Sex‐related differences in response to zinc pyrithione shampoo vs. non‐anti‐dandruff shampoo. (27th December 2018) - Collins, L. Z.; Baines, F. L.; Matheson, J. R.; Turner, G. A.; Diao, Y.; Li, Y.; Pi, Y.
Abstract: Objective: Sex‐related differences in skin properties may be expected to impact dandruff formation and treatment. A meta‐analysis approach was undertaken to investigate potential differences between males and females in response to zinc pyrithione (ZnPT) treatment vs. non‐anti‐dandruff (AD) shampoo. A separate pooled statistical analysis of ceramide and total protein loss endpoints was also undertaken to assess potential sex‐related differences in stratum corneum properties that might influence response to ZnPT vs. non‐AD shampoo in subjects with dandruff. Methods: The meta‐analysis approach included data from 17 half‐head, double‐blind, randomized studies ( N = 2088) undertaken in Asia to assess the effectiveness of 1% ZnPT shampoo and/or non‐AD shampoo in reducing dandruff severity, as assessed by Total Weighted Head Score Adherent Flake (TWHS‐AF) methodology. Treatment duration was 4 weeks, with TWHS‐AF measured at weekly intervals. Data from an additional three studies ( N = 143) conducted in Asia were included in the pooled analysis of ceramide levels and protein loss from scalp skin of subjects with dandruff. Results: Response to 1% ZnPT vs. non‐AD shampoo was greater in males than in females at all time points; after 4 weeks, the between‐treatment difference in TWHS‐AF was −17.5 (95% confidence interval [CI] −19.5, −15.5) in males and −11.1 (−13.2, −8.9) in females. Sex‐related differences were observed between males and females in response to both 1% ZnPT and non‐AD shampoos. Males had a stronger response than females to treatment with 1% ZnPT shampoo, while dandruff decreased to a greater extent in females than in males when using non‐AD shampoo. Statistically significant sex‐related differences in ceramide levels and total protein loss were observed (both P < 0.01). Ceramide levels were 0.76 times lower (95% CI 0.60, 0.97) in males than in females, while total protein loss was 1.4 times greater (95% CI 1.1, 1.9) in males than in females. Conclusion: Males show a greater response than females to 1% ZnPT shampoo, while females show a greater response than males to non‐AD shampoo. These findings may in part be explained by the sex‐related differences observed in stratum corneum properties, which may make males more prone to dandruff than females.